Professional Development Of An Educational Psychologist In The System Of Psychological And Counseling Service Of The University - Anatoliyevna Repkina, Yulia (2021)
The priority goal of modernizing the Russian education system is to ensure a high quality of knowledge. The psychological and counseling service is capable of implementing many qualitative changes in the higher education system. The development of the psychological and counseling service is due to its role in the modernization of Russian education, on the one hand, and the growing need for educational psychologists, on the other. The outflow of psychologists from the education system negatively affects the quality of the services and the image of the psychological and counseling service in education and society as a whole. Consequently, the career and personal development of a psychologist in the educational organization of higher education requires special research. The psychological support for an entry-level psychologist is necessary during the period of his/her professional development. The peculiarities of the psychological and counseling service require that a psychologist independently identify the directions and priorities of professional activity and show initiative in organizing the work and assessing its effectiveness. This, as a rule, is difficult for an entry-level educational psychologist. Certain difficulties for an entry-level psychologist are associated with the specifics of professional psychological and counseling activity. The tools of the professional activity of a trained psychologist are the personal and professional qualities, skills and abilities. Therefore, specific requirements are imposed on the personal and professional qualities of a psychologist. At the same time, in the professional environment, there are no unified standards for the personality of a psychologist and criteria for assessing the degree of his/her professionalism. Despite the constant updating of research in the field of psychological support for education, the identification of the necessary conditions for the training of a high-level specialist, the contradiction between the demand of modern society for a well-trained specialist and the insufficient level of readiness of young specialists for productive professional activity is deepening. An educational psychologist beginning to work at a university turns out to be unable to interact in a professional environment and experiences difficulties in establishing contacts with students and their parents.